A bifunctional DNA probe for sensing pH and microRNA using a nanopore. Issue 21 (1st September 2020) - Zhang, Yun; Song, Peng; Guo, Bingyuan; Hao, Wenying; Liu, Lei; Wu, Hai-Chen
Abstract : We have developed a bifunctional probe based on triplex molecular beacons for the measurement of environmental pH and quantification of microRNA-10b using a nanopore. Abstract : We have developed a bifunctional probe based on triplex molecular beacons for the measurement of environmental pH and quantification of microRNA-10b using a nanopore. The probe responds sharply to solution pH changes in the range of 6.0–7.5. The limit of detection for microRNA-10b is as low as 5.0 pM.